Challenges of Stem-cell-based Craniofacial Regeneration - Xu, Ruoshi; Zhou, Chenchen; Zhang, Yuning; Zhang, Shiwen; Xie, Jing; Yuan, Quan (Current Stem Cell Research & Therapy, 2021)
Oral diseases, such as dental caries, pulpitis, periodontitis, and craniofacial trauma, are common. Some individuals suffer from oral cancer or congenital craniofacial defects. The oral-systemic disease link reveals that a dental disorder is not a minor problem. Tissue loss is an inevitable consequence of most oral diseases, and repairing the tissue loss and restoring craniofacial function are highly expected by patients and are terminal targets of dental treatment. The current clinical approach for tissue loss due to dental caries, pulpitis, periodontitis, oral cancer, trauma, and developmental diseases depends on the filling of corresponding material, allograft, or autograft bone after lesion removal. Repair of the tissue volume is expectedly followed by promising functional restoration using regenerative dental tissue or tissue engineering, which has currently aroused the interest of clinicians and researchers. This review focuses on the ideas and recent findings on newly identified skeletal stem cells (SSCs) as candidates for craniofacial regeneration, signaling regulation of SSCs extended from embryonic development, and signal molecule delivery for the repair of the craniofacial defect, sincerely hoping that the hypothesis of craniofacial self-healing is true in the future.
Keywords: craniofacial regeneration